PCR amplicons identify widespread copy number variation in human centromeric arrays and instability in cancer - Leonardo Gomes de Lima; Edmund Howe; Vijay Pratap Singh; Tamara Potapova; Hua Li; Baoshan Xu; Jemma Castle; Steve Crozier; Christine J. Harrison; Steve C. Clifford; Karen H. Miga; Sarra L. Ryan; et al. (Elsevier, 2021)
Summary: Centromeric α-satellite repeats represent ∼6% of the human genome, but their length and repetitive nature make sequencing and analysis of those regions challenging. However, centromeres are essential for the stable propagation of chromosomes, so tools are urgently needed to monitor centromere copy number and how it influences chromosome transmission and genome stability. We developed and benchmarked droplet digital PCR (ddPCR) assays that measure copy number for five human centromeric arrays. We applied them to characterize natural variation in centromeric array size, analyzing normal tissue from 37 individuals from China and 39 individuals from the US and UK. Each chromosome-specific array varies in size up to 10-fold across individuals and up to 50-fold across chromosomes, indicating a unique complement of arrays in each individual. We also used the ddPCR assays to analyze centromere copy number in 76 matched tumor-normal samples across four cancer types, representing the most-comprehensive quantitative analysis of centromeric array stability in cancer to date. In contrast to stable transmission in cultured cells, centromeric arrays show gain and loss events in each of the cancer types, suggesting centromeric α-satellite DNA represents a new category of genome instability in cancer. Our methodology for measuring human centromeric-array copy number will advance research on centromeres and genome integrity in normal and disease states.